2016
DOI: 10.1007/s00167-016-4370-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical options for chronic patellar tendon rupture in total knee arthroplasty

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Among the patients in whom we performed revision for extensor mechanism problems, eighth (72%) had patellar instability, one (9%) had patellar fracture and two (18%) had patellar tendon rupture as the primary diagnosis. Patellar tendon injuries occurring during exposure and when the patella is turned down laterally during revision surgery have been reported in the literature at variable rates (24).Halder performed tibial tubercle osteotomy in 67 RKAS patients and encountered pseudoarthrosis in only one case, consistent with performing the surgical technique correctly. Tibial tubercle osteotomy was defined as a safe and effective technique in patients with contracture, in whom the knee cannot be opened with the standard medial and lateral parapatellar approach (25,26).…”
Section: Discussionmentioning
confidence: 87%
“…Among the patients in whom we performed revision for extensor mechanism problems, eighth (72%) had patellar instability, one (9%) had patellar fracture and two (18%) had patellar tendon rupture as the primary diagnosis. Patellar tendon injuries occurring during exposure and when the patella is turned down laterally during revision surgery have been reported in the literature at variable rates (24).Halder performed tibial tubercle osteotomy in 67 RKAS patients and encountered pseudoarthrosis in only one case, consistent with performing the surgical technique correctly. Tibial tubercle osteotomy was defined as a safe and effective technique in patients with contracture, in whom the knee cannot be opened with the standard medial and lateral parapatellar approach (25,26).…”
Section: Discussionmentioning
confidence: 87%
“…The advantage of an Achilles tendon allogeneic transplant is that it provides the graft with good tissue and bone quality in patients whose tissues are particularly fragile. Lamberti et al demonstrated in their recent article that allografts in general, and Achilles tendon allografts in particular, provided better functional results than autografts in restoring correct joint function following total knee arthroplasty [ 16 ]. They also reported good results by performing an ipsilateral quadriceps and semitendinosus autograft using the Rajgopal et al technique [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, in chronic lesions, knee extensor mechanism reconstruction can usually be performed using allogenic or synthetic grafts and the gold standard for treatment in these cases is utilization of Achilles's tendon allografts. 23 Allografts can be fresh-frozen or freeze-dried; the Achilles's tendon or the complete extensor mechanism are the suitable grafts. In TKA, the Achilles's tendon was found to provide reliable reconstruction of ruptured patellar tendon.…”
Section: Discussionmentioning
confidence: 99%